Badanie związków polityki i prawa jako przedmiot nauki administracji - Kusiak-Winter, Renata (PRAWO i WIĘŹ, 2024)
By abolishing the science of administration as a separate scientific discipline within the field of legal sciences, the legislator undermined the legitimacy of the hitherto very rich research perspective on the various and heterogeneous conditions in which public administration functions. After the reform, everything that did not fall within the scope of administrative law was assigned to the newly created science of politics and administration. As a result of this division, there is a danger of „underdeveloped research areas” in which, according to the author, the question of the relationship between politics and law can be included. On the one hand, there is a temptation for lawyers to overlook phenomena in public administration that are related to politics and at the same time are not directly related to administrative law. On the other hand, one should be aware that the analysis of the research conducted so far in political science shows a notorious tendency to marginalize the legal threads that condition the functioning of public administration. This study is another voice in the discussion on the restoration of the science of administration as a separate scientific discipline.